Secukinumab Treatment in Patients With Hidradenitis Suppurativa in Real-World Clinical Settings: A Multicenter Study - Erbağcı, Ece; Karstarlı Bakay, Özge Sevil; Hapa, Fatma Aslı (Dermatology Practical & Conceptual, 2025)
Introduction: Treatment of hidradenitis suppurativa (HS) remains a challenge in clinical practice for dermatologists. Although the efficacy and safety of secukinumab (SEC) in the treatment of HS has been demonstrated in phase III studies, real-world data is limited. Objectives: We conducted a retrospective multicenter study to evaluate the efficacy and safety of SEC treatment in HS patients in real-world settings. Methods: Adult patients who were diagnosed with HS and used SEC for at least 3 months were included in the study. Results: A total of 31 patients were included in the study; 14 of them (45.2%) were female. The mean age was 39.32 ± 10.26 years, and the mean disease duration was 11.77 ± 7.99 years. Nine (29%) patients were biologic-naive and 10 (32.3%) were adalimumab-naive. Disease severity was Hurley I in 7 patients (22.6%), Hurley II in 9 patients (29%), and Hurley III in 15 patients (48.4%). The Hidradenitis Suppurativa Clinical Response (HiSCR) was achieved in 20 patients (64.5%) in the third month of treatment. SEC treatment was discontinued due to primary ineffectiveness in 9 (29%) patients, secondary ineffectiveness in 1 (3.2%) patient, adverse effects in 1 (3.2%) patient, and loss of follow-up in 1 (3.2%) patient. Paradoxical pyoderma gangrenosum was observed as an adverse effect in 1 patient that resolved after discontinuing SEC and starting infliximab. Conclusion: SEC appears to be an effective and safe treatment option for HS, especially when used in the early and mild stages of the disease and in biologic-naive patients.